The diverse pathways of higher education students: a sociological analysis on inequality, context and agency - Costa, A. F.; Lopes, J. T. (Portuguese Journal of Social Science, 2011)
One of the consequences of the extension of access to higher education in Portugal, as in other countries, has been the diversification of students’ social background. This process has not led to the elimination of social inequalities in students’ access to and success in higher education, but those inequalities have not remained the same. In fact, there have been some highly significant and complex changes in this area. To study them, we carried out a comprehensive sociological investigation that covers the entire Portuguese higher education system – including universities and polytechnics – covering different areas of knowledge in different regions. The theoretic model included three levels of analysis: structural, institutional and biographical. The research design involved quantitative and qualitative methodological procedures. At the biographical level, in-depth interviews were conducted with 170 students. From these interviews we drew ‘sociological portraits’ and built analytical types both of these students’ structural and institutional positioning in their educational path and of how they actively shaped diverse types of personal trajectories. The identification of these types of student paths may help advance knowledge in this field, shedding considerably more light than the usual administrative categories of ‘success’, ‘failure’ and ‘dropout’